Depati Amir and Chinese Peopleâs Resistance against Dutch Colonialism in Bangka, 1848â1851: An Archival Study - Madjid, M. Dien (TAWARIKH, 2017)
ABSTRACT: Since many years ago, Bangkaâs tin had been recognized as one of prior commodities having been known by people outside Nusantara (Indonesian archipelago). Due to its high economic value, this natural resource had invited the other huge power from outside this island, intending to have control over it. In the 19th century, the map of political power in this island changed, along with the strengthening of colonial influence. Their political authority was connected to the maintaining of tin trenches. People were asked to obey the colonial provisions, as undergone by Chinese mining laborers. The difficulty suffered by the people and Bangka Chinese laborers had caused Depati Amir to struggle to resist against the imbalance. The battle was then continued by Depati Amir who tried to fight the colonial power in Bangka. One of the sources of Dutch power was their ability in developing administrative communication. Correspondences and report arrangement became the references to make the next fighting scheme. Later these reports were then used to be the primary references to reveal the activities of Depati Amir, Chinese laborers, and Dutch government in Bangka. This paper is based on the findings of a research some time ago, discussing about the struggle of Depati Amir and Chinese people againts Dutch colonial government in the mid of 19th century. The findings showed that âthe archive tells the storyâ, that is by showing the contents of archives as a material to understand the story of Depati Amir and his cooperation with Chinese people in overthrowing the wall of Dutch colonialism.Â  KEY WORDS: Depati Amir; Chinese People; Dutch Colonialism; Resistance; Archive Tells the Story.About the Author: Prof. Dr. M. Dien Madjid is a Lecturer at the Faculty of Adab and Humanities UIN (State Islamic University) Syarif Hidayatullah, Jalan Ir. H. Djuanda No.95, Ciputat, Kota Tangerang Selatan 15412, Banten, Indonesia. For academic interests, the author is able to be contacted via his e-mail at: dienmadjid@uinjkt.ac.idÂ Recommended Citation: Madjid, M. Dien. (2017). âDepati Amir and Chinese Peopleâs Resistance against Dutch Colonialism in Bangka, 1848â1851: An Archival Studyâ in TAWARIKH: International Journal for Historical Studies, Vol.9(1), October, pp.33-48. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Article Timeline: Accepted (February 17, 2017); Revised (May 20, 2017); and Published (October 28, 2017).